Observer based Feedback Control of Biodynamical Model of Tumor Growth with Sampled Measurements - Gholami, Shahrzad; Alasty, Aria; Salarieh, Hassan (European Control Conference (ECC), 2016)
This paper deals with the cancer treatment scheduling via observer-based feedback control of a tumor growth biodynamical model. An experimental nonlinear model is utilized to design a feedback controller. This model was validated by a pharmacological study on xenograft models obtained by transplantation of colon carcinoma cell lines in athymic mice. Input-output feedback linearization approach is used to linearize the nonlinear model of the system and design a control law. It is assumed that tumor weight can be measured in definite intervals. So a continuous-discrete observer is designed to estimate states of the system based on discrete sampled data which are tumor weight in this case. To investigate the effect of the drug on the normal cells, a body weight toxicity model is considered to be checked during the simulation. Finally, a discrete chemotherapy dose schedule is proposed. Simulation results show the effectiveness of the proposed observer-controller algorithms.